2015
DOI: 10.1542/peds.2014-3099
|View full text |Cite|
|
Sign up to set email alerts
|

Utility of Symptoms to Predict Treatment Outcomes in Obstructive Sleep Apnea Syndrome

Abstract: BACKGROUND AND OBJECTIVES: Polysomnography defines the pathophysiology of obstructive sleep apnea syndrome (OSAS) but does not predict some important comorbidities or their response to adenotonsillectomy. We assessed whether OSAS symptoms, as reflected on the Sleep-Related Breathing Disorders Scale of the Pediatric Sleep Questionnaire (PSQ), may offer clinical predictive value.METHODS: Baseline and 7-month follow-up data were analyzed from 185 participants (aged 5-9 years with polysomnographically confirmed OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
85
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 21 publications
(8 reference statements)
3
85
0
7
Order By: Relevance
“…The results provide impetus for more research on the cognitive and neurobiological effects of AT for pediatric OSAS. 5,10,29,44 The findings are also consistent with previous research suggesting that tests of nonverbal reasoning, attention, and fine motor skills are selectively affected by OSAS and thus more likely to improve after AT.…”
Section: Discussionsupporting
confidence: 89%
“…The results provide impetus for more research on the cognitive and neurobiological effects of AT for pediatric OSAS. 5,10,29,44 The findings are also consistent with previous research suggesting that tests of nonverbal reasoning, attention, and fine motor skills are selectively affected by OSAS and thus more likely to improve after AT.…”
Section: Discussionsupporting
confidence: 89%
“…In the CHAT study, changes in the attention and executive function objective scores from baseline to follow-up did not differ between the early-adenotonsillectomy and the watchful-waiting study groups (class I) [126]. However, there was a significant improvement in executive functioning, attention, behaviour and excessive daytime sleepiness as rated by parents, which was predicted by the preoperative severity of symptoms but not by the AHI (class I) [113,177]. Similarly, two systematic reviews of mostly class III and IV studies concluded that adenotonsillectomy is followed by improvements in behavioural problems and neurocognitive skills irrespective of SDB severity [178,179].…”
Section: 4mentioning
confidence: 92%
“…c) A positive respiratory polygraphy or nocturnal oximetry in the context of clinical symptoms indicative of obstructive SDB has been used as an indication for adenotonsillectomy (class III or IV) [136,162,184]. Results of the CHAT study indicate that improvements in morbidity from the central nervous system, quality of life and symptoms of SDB occur post-adenotonsillectomy regardless of the severity of abnormalities in preoperative polysomnography (class I) [113,177].…”
Section: 4mentioning
confidence: 99%
“…As for OSA, the PSQ showed a sensitivity of 77% to 81% and a specificity of 87% compared to PSG. 13,33 Obviously, physiologic evaluation by objective PSG is needed to diagnose OSA and should be applied in future studies as the main outcome measure. Nevertheless, the symptoms obtained during office visit by the structured PSQ offer adjunctive insight into important comorbidities and likely surgical responses, 33 and hence may be used in addition.…”
Section: Discussionmentioning
confidence: 99%